2022
DOI: 10.1177/17470218221142145
|View full text |Cite
|
Sign up to set email alerts
|

Letter-similarity effects in braille word recognition

Abstract: Letter-similarity effects are elusive with common words in lexical decision experiments: viotin and viocin (base word: violin) produce similar error rates and rejection latencies. However, they are robust for stimuli often presented with the same appearance (e.g., misspelled logotypes such as anazon [base word: amazon] produce more errors and longer latencies than atazon). Here, we examine whether letter-similarity effects occur in reading braille. The rationale is that braille is a writing system in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…They found that transposed-letter pseudowords were classified less accurately and slower than replaced-letter pseudowords, showing that the noise associated with letter position coding in word recognition is not purely perceptual, and supporting the idea that serial order processing is a universal mechanism. In the second study (Baciero et al 2022b), mispelled braille words were classified less accurately when the replaced letter was tactually similar to the original letter than when it was dissimilar 5 , thus revealing that the uncertainty during letter encoding in braille word recognition is not resolved as quickly as with common words in visual-word recognition (see Perea et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that transposed-letter pseudowords were classified less accurately and slower than replaced-letter pseudowords, showing that the noise associated with letter position coding in word recognition is not purely perceptual, and supporting the idea that serial order processing is a universal mechanism. In the second study (Baciero et al 2022b), mispelled braille words were classified less accurately when the replaced letter was tactually similar to the original letter than when it was dissimilar 5 , thus revealing that the uncertainty during letter encoding in braille word recognition is not resolved as quickly as with common words in visual-word recognition (see Perea et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While there was a strong flanker effect, its temporal dynamics differ from those results found in the visual modality, thus suggesting the cognitive mechanisms that underlie this effect are guided by both modality-general and modality-specific processes. To examine braille orthographic processing, Baciero et al (2022aBaciero et al ( , 2022b tested skilled braille readers in two lexical decision studies. In the first one they created pseudowords by either transposing or replacing two adjacent letters of a word (e.g., aveinda vs. avearda, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the representation of stimuli that keep some homogeneity in the visual format, like city names can be susceptible (to a lesser degree) to visual elements (e.g., Barcetona would activate Barcelona more than Barcesona, at least with relatively brief exposure durations). Interestingly, this interpretation can easily explain why misspellings in common words in braille produce a tactile letter similarity effect (Baciero et al, 2022 ): braille letters have a characteristic homogeneous format (e.g., see UK Association for Accessible Formats, 2017 ), thus making them more sensitive to perceptual effects.…”
Section: Discussionmentioning
confidence: 99%